2010
DOI: 10.1073/pnas.0915133107
|View full text |Cite
|
Sign up to set email alerts
|

A defunctioning polymorphism in FCGR2B is associated with protection against malaria but susceptibility to systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease more prevalent in people of African and Asian origin than Caucasian origin. FcγRIIb is an inhibitory Fc receptor with a critical role in immune regulation. Mouse data suggest that FcγRIIb deficiency increases susceptibility to autoimmune disease but protects against infection. We show that a SNP in human FCGR2B that abrogates receptor function is strongly associated with susceptibility to SLE in both Caucasians and Southeast Asians. The min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
148
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 37 publications
11
148
0
1
Order By: Relevance
“…A single nucleotide polymorphism in the gene encoding the human FcγRIIB that abrogates receptor function is strongly associated with susceptibility to SLE in both Caucasians and Southeast Asians (13). Willcocks et al (12) recently reported that the minor allele of this polymorphism is more common in Southeast Asians and Africans than in Caucasians and that homozygosity for the minor allele is associated with substantial protection from severe malaria in children in Kenya (12), although this study was not powered to detect associations with a specific type of severe malaria, for example cerebral malaria versus severe malaria anemia. Consistent with the observation by Willcocks et al, it was shown earlier that macrophages from individuals homozygous for this polymorphism efficiently engulfed Pf trophozoites (11).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A single nucleotide polymorphism in the gene encoding the human FcγRIIB that abrogates receptor function is strongly associated with susceptibility to SLE in both Caucasians and Southeast Asians (13). Willcocks et al (12) recently reported that the minor allele of this polymorphism is more common in Southeast Asians and Africans than in Caucasians and that homozygosity for the minor allele is associated with substantial protection from severe malaria in children in Kenya (12), although this study was not powered to detect associations with a specific type of severe malaria, for example cerebral malaria versus severe malaria anemia. Consistent with the observation by Willcocks et al, it was shown earlier that macrophages from individuals homozygous for this polymorphism efficiently engulfed Pf trophozoites (11).…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, FcγRIIB deficiency in mice has been shown to reduce the severity of nonfatal Plasmodium chabaudi infections that correlated with increased levels of the proinflammatory cytokine TNF-α and with increased antibody levels (11). Willcocks et al (12) recently provided evidence that a loss-of-function polymorphism in FcγRIIB is associated with protection from severe malaria in African children. In addition to the FcγRIIB deficiency, FcγRIIB −/− .yaa mice have the Y chromosome-linked genetic modifier Yaa, a duplication in the gene that encodes Toll-like receptor 7 (TLR7) (14), a member of one family of the innate immune system's pathogen-associated molecular pattern recognition receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated VEGF-A has been noted in patients with rheumatoid arthritis and SLE and correlates with disease activity (24,25). In humans, a nonsynonymous SNP in FCGR2B (rs1050501) (isoleucine to threonine at position 232) leads to receptor dysfunction and confers susceptibility to SLE (5,26). We hypothesized that rs1050501 would affect VEGF-A production in individuals with the SLE-associated FcγRIIB T232 receptor.…”
Section: Fcγriib Expression On Macrophages Rather Than B Cells Moderatesmentioning
confidence: 99%
“…It is interesting to note that rs1050501, a nonsynonymous SNP at position 161643798 in the genomic region encoding the transmembrane segment of FcγRIIb (Ile232Thr), is a strong risk factor for systemic lupus in multiple East Asian populations, but not in white populations 16,17 . It lies between rs1771568 and rs10917686 (see Table 2 1 , Kim and Bang) and might be involved in the proposed association of rs6697139 with therapeutic response.…”
Section: Rheumatologymentioning
confidence: 99%